What Drives Carbon-Reducing Investments? A Vignette Experiment on Managers' Decision-Making From a Multilevel Perspective - Rüdiger Hahn; Thomas Pioch; Daniel Reimsbach; Frank Schiemann (Business Strategy and the Environment, 2025)
Our study aims to shed light on the factors that drive managers' sustainability-related decision-making. We take a multilevel perspective, analyzing individual-, organizational-, and institutional-level factors, which allows us to present a coherent account of a complex environment of influential factors. Based on an explorative vignette experiment with professional managers in a setting related to carbon-reducing investments, we find that certain individual-level factors, such as managers' biospheric orientation or a strong belief in business ethics, are associated with higher carbon-reducing investments. However, these individual-level factors do not alter the overall influence of organizational- and institutional-level factors. The financial impact of carbon-reducing investments—at the organizational level—as well as the number of carbon-conscious investors and the regulatory disclosure regime in which a firm operates—at the institutional level—significantly drive managers' investment decisions. We find only a few instances in which specific factor combinations are decision-relevant. These findings have important implications for research and policymaking with regard to improving corporate sustainability in general and particularly reducing corporate carbon emissions.
Keywords: 330; carbon management; carbon-reducing investment; sustainability disclosure; vignette study